Occurrence of Delphastus davidsoni (Coleoptera: Coccinellidae) predating Bemisia tabaci biotype B (Hemiptera: Aleyrodidae) in greenhouse conditions in Brazil. - Baldin, Edson Luiz Lopes [UNESP]; Schlick-souza, E.C.; Fujihara, R.T.; Lourencao, A.L.; Gonzalez F., G. (My University, 2011)
In March of 2009 larvae and adults from ladybug Delphastus davidsoni Gordon (Coleoptera: Coccinellidae) were observed predating eggs and nymphs of Bemisia tabaci (Gennadius) biotype B (Hemiptera: Aleyrodidae) in cabbage plants on rearing of this whitefly. This is the first report of D. davidsoni predating B. tabaci biotype B on cabbage plants, limiting the rearing and showing high potential on biological control of this aleyrodid for conditions of protected cultivation.